METODE BOARDING SCHOOL SEBAGAI SARANA PENUNJANG KEBERHASILAN PENDIDIKAN AKHLAK SISWA DI MAN 2 PASURUAN - Zakiyah, Riska Hany (Muta'allim: Jurnal Pendidikan Agama Islam, 2022)
Boarding school is a school in which religious knowledge is studied in detail, both worship practices, muamalah and morals, but learning at boarding schools or boarding schools does not lag behind general knowledge as in other public schools. With the existence of Islamic boarding school education, it is expected to be able to maintain human morals so that they have good character, because in Islamic boarding schools the students are specifically taught religious knowledge how humans should have good relations with Allah swt., and have good relations with humans. The aims of this study were to: (1) To determine the role of boarding schools in supporting the success of moral education for students at MAN 2 Pasuruan. (2) To find out the factors that support and hinder the success of moral education for the students of MAN 2 Pasuruan. (3) To find out what method the boarding school uses to support the success of moral education for the students of MAN 2 Pasuruan. This research uses a qualitative approach with a descriptive type of research. Data collection techniques in this study used observation, interviews, and documentation techniques. The data that has been obtained is then analyzed by the steps of data reduction, data presentation, and drawing conclusions. The validity of the data in this study used a triangulation technique. The results showed that: (1) The role of boarding schools in supporting the moral education of students at MAN 2 Pasuruan is that the boarding school system really supports the process of forming students' morals through coaching in the dormitory including the habit of doing fardhu prayers in congregation and sunnah prayers, and others. (2) Factors supporting the success of moral education for students at MAN 2 Pasuruan, namely: a) The existence of moral aqidah subjects, b) The existence of the Tahfidzul Qur'an program, c) The support of parents in sending their children to boarding schools. The inhibiting factors for the success of students' moral education at MAN 2 Pasuruan are: a) Friends association factors, b) Lack of communication between teachers and parents, c) Physical condition factors. (3) The methods used by boarding schools to support the success of moral education for MAN 2 Pasuruan students are: a) exemplary method, b) advice method, c) reward and punishment method Abstrak Boarding school merupakan sekolah yang di dalamnya mempelajari ilmu agama secara rinci baik praktik ibadah, muamalah serta akhlak, akan tetapi pembelajaran di boarding school atau pesantren tidak tertinggal pula ilmu umum seperti yang ada pada sekolah umum lainnya. Dengan adanya pendidikan pondok pesantren, maka diharapkan mampu mempertahankan akhlak manusia agar berakhlak baik, karena dalam pesantren para santri secara khusus diajarkan ilmu agama bagaimana seharusnya manusia berhubungan baik dengan Allah swt., dan berhubungan baik dengan manusia. Tujuan penelitian ini adalah untuk: (1) Untuk mengetahui peran boarding school dalam menunjang keberhasilan pendidikan akhlak siswa MAN 2 Pasuruan. (2) Untuk mengetahui faktor-faktor yang menjadi penunjang dan penghambat keberhasilan pendidikan akhlak siswa MAN 2 Pasuruan. (3) Untuk mengetahui metode apa yang dilakukan boarding school untuk menunjang keberhasilan pendidikan akhlak siswa MAN 2 Pasuruan. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Teknik pengumpulan data dalam penelitian ini menggunakan teknik observasi, wawancara, dan dokumentasi. Data yang telah diperoleh kemudian dianalisis dengan langkah-langkah yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Adapun keabsahan data dalam penelitian ini menggunakan teknik triangulasi teknik. Hasil penelitian menunjukkan bahwa: (1) Peran boarding school dalam menunjang pendidikan akhlak siswa di MAN 2 Pasuruan adalah dengan adanya sistem boarding school sangat menunjang proses pembentukan akhlak siswa melalui pembinaan di asrama meliputi pembiasaan melakukan salat fardhu berjamaah dan salat sunnah, dan lain-lain. (2) Faktor penunjang keberhasilan pendidikan akhlak siswa di MAN 2 Pasuruan yaitu: a) Adanya mata pelajaran akidah akhlak, b) Adanya program Tahfidzul Qur’an, c) Dukungan orang tua memasukkan anak ke pondok. Faktor penghambat keberhasilan pendidikan akhlak siswa di MAN 2 Pasuruan yaitu: a) Faktor pergaulan teman, b) Faktor Kurangnya komunikasi antara guru dan orang tua, c) Faktor kondisi fisik. (3) Metode yang dilakukan boarding school untuk menunjang keberhasilan pendidikan akhlak siswa MAN 2 Pasuruan yaitu: a) Metode keteladanan, b) Metode nasehat, c) Metode reward dan punishment.